Dumbbell-Shaped Rhabdomyosarcoma: Two-Stage Surgical Resection - ElFiky, Mahmoud (European Journal of Pediatric Surgery Reports, 2015)
Female neonate admitted to our hospital with an abdominal mass and a thigh mass that were connected as a single dumbbell-shaped mass. CT was done on admission that showed cystic swelling in the thigh with intra-abdominal extension passing under inguinal ligament, most probably lymphangioma.The patient was assessed and prepared for surgery starting with the abdominal part then after two days for the thigh mass. Distal pulses in the lower limbs were assessed intra- and postoperatively following both surgeries. The pathology report showed rhabdomyosarcoma of the embryonal type.
Keywords: Rhabdomyosarcoma; Neonate; Tumor; Surgery